Mentality as a subject of interdisciplinary research: definition issue - I. V. Zhyvohliadova (Ukrainian Cultural Studies, 2017)
Mentality as an essential mechanism of cultural and social processes, approaches to the definition of this phenomenon are analyzed. The purpose of the article is the reconstruction of the history of social and humanitarian focused research that is devoted to the problem of mentality, the development of its theory and specifically practical analysis. Historical, systematic, typological and comparative analysis methods are applied. The variety of knowledge about mentality demonstrates the breadth of the limits of its manifestation in different spheres of human activity. The mentality originality research within different sectors of social and humanitarian knowledge, analysis of its structure and mechanisms of functional fullness, dialectic interrelation between spiritual entities claim the right to the independent existence of this phenomenon as a special representant of spiritual activity. We support the focus of studies that attempts to reveal the "human" sense of this phenomenon. Expanding knowledge of the nature, methods of formation, assimilation and simulation mental complexes allows to differentiate cultures, that in turn facilitates the identification and understanding of the actual mechanisms of cultural and civilizational processes. Research of mentality makes it possible to understand not so much "that" some person or group knows, imagines, thinks, but how much "how", "whereby" it experiences, interprets, operates. Not by chance, most scientists consider the mentality as a special metalanguage of certain specific culture that determines the nature of the understanding, emotions and actions both individual and entire groups. It is mentality that is one of the determining factors of society recreation, the existence of a particular kind of culture in general depends on its ability to function in this capacity.
Keywords: spirituality, mentality, national character